Systematic Approach for Web Protection Runtime Tools’ Effectiveness Analysis - Sureda Riera, Tomás; Bermejo Higuera, Juan Ramón; Bermejo-Higuera, Javier; Sicilia, Juan Antonio; Martínez Herraiz, José-Javier (CMES - Computer Modeling in Engineering and Sciences, 2023)
Web applications represent one of the principal vehicles by which attackers gain access to an organization’s network or resources. Thus, different approaches to protect web applications have been proposed to date. Of them, the two major approaches are Web Application Firewalls (WAF) and Runtime Application Self Protection (RASP). It is, thus, essential to understand the differences and relative effectiveness of both these approaches for effective decision-making regarding the security of web applications. Here we present a comparative study between WAF and RASP simulated settings, with the aim to compare their effectiveness and efficiency against different categories of attacks. For this, we used computation of different metrics and sorted their results using F-Score index. We found that RASP tools scored better than WAF tools. In this study, we also developed a new experimental methodology for the objective evaluation of web protection tools since, to the best of our knowledge, no method specifically evaluates web protection tools.
Keywords: experimental methodology; F-Score; Runtime Application Self Protection (RASP); Web Application Firewall (WAF); web attacks; Scopus; JCR